Increased placental mitochondrial fusion in gestational diabetes mellitus: An adaptive mechanism to optimize feto-placental metabolic homeostasis? - Abbade, Joelcio [UNESP]; Klemetti, Miira Marjuska; Farrell, Abby; Ermini, Leonardo; Gillmore, Taylor; Sallais, Julien; Tagliaferro, Andrea; Post, Martin; Caniggia, Isabella (BMJ, 2020)
Introduction Gestational diabetes mellitus (GDM), a common pregnancy disorder, increases the risk of fetal overgrowth and later metabolic morbidity in the offspring. The placenta likely mediates these sequelae, but the exact mechanisms remain elusive. Mitochondrial dynamics refers to the joining and division of these organelles, in attempts to maintain cellular homeostasis in stress conditions or alterations in oxygen and fuel availability. These remodeling processes are critical to optimize mitochondrial function, and their disturbances characterize diabetes and obesity. Methods and results Herein we show that placental mitochondrial dynamics are tilted toward fusion in GDM, as evidenced by transmission electron microscopy and changes in the expression of key mechanochemical enzymes such as OPA1 and active phosphorylated DRP1. In vitro experiments using choriocarcinoma JEG-3 cells demonstrated that increased exposure to insulin, which typifies GDM, promotes mitochondrial fusion. As placental ceramide induces mitochondrial fission in pre-eclampsia, we also examined ceramide content in GDM and control placentae and observed a reduction in placental ceramide enrichment in GDM, likely due to an insulin-dependent increase in ceramide-degrading ASAH1 expression. Conclusions Placental mitochondrial fusion is enhanced in GDM, possibly as a compensatory response to maternal and fetal metabolic derangements. Alterations in placental insulin exposure and sphingolipid metabolism are among potential contributing factors. Overall, our results suggest that GDM has profound impacts on placental mitochondrial dynamics and metabolism, with plausible implications for the short-term and long-term health of the offspring.
Keywords: GDM; mitochondria; placenta